Aerodynamic stability of ice-accreted bridge cables. (January 2015) - Demartino, C.; Ricciardelli, F.
Abstract: The prediction of galloping instability is usually based on a quasi-steady approach, in which instantaneous wind forces are derived from the aerodynamic force coefficients obtained in static wind tunnel tests. Several galloping models exist, that differ for the degrees of freedom and for the geometric and aerodynamic characteristics considered. The aim of this paper is twofold: first, it compares the background hypotheses of the different galloping models, and the results they produce. This is done though an application to ice-accreted bridge cables, the analysis of the stability of which is the second aim of the paper. Wind tunnel data obtained by the authors for bridge hangers and stay cables are used in the calculations. As to the comparison among the different models, not existing a benchmark, the research is not aimed at judging the quality of each of them, but rather at pointing out the differences they bring and at discussing their most appropriate application. Abstract : Highlights: We compared the background hypotheses of the different galloping models. The galloping models were applied to ice accreted bridge cables comparing results. Stability of bridge hangers and stay cables was investigated.